CHILD LABORERS ACCESS TO EDUCATION IN KANDAHAR CITY - Nabavi, Salman Ali; Mohammadi, Alinaqi; Achak, Jailani; Sail, Ezatullah (American International Journal of Social Science Research, 2021)
This study describes the child laborers’ access to education in Kandahar city. We present the methodology followed in the study, study area and type of data collected to estimate to dimensions of child laborers access to education in the city. Data collected contains information about sociodemographic characteristics, Child laborer access to education, negative impacts of working on children’s education and Head of household education. It is hoped that this study would intensify a debate on main barriers to education that could tie in with analysis and commentary on providing education and related facilities to marginalized groups like child laborers and girls in society. Readers are encouraged to consider how to understand the landscape that child laborers are confronting, while also asking critical questions about the socio-political circumstances and inefficiency of educational system in which we all participate as we fight to eliminate marginalization and illiteracy in the society. Finally, it is recommended that there is a need to re-vision of the schooling system in order to evolve ways and means of offering education that is inclusive and relevant for working children in Kandahar city and other similar context.